Association of Plasma Branched-Chain Amino Acid With Biomarkers of Inflammation and Lipid Metabolism in Women. (15th July 2021) - Hamaya, Rikuta; Mora, Samia; Lawler, Patrick R.; Cook, Nancy R.; Ridker, Paul M.; Buring, Julie E.; Lee, I-Min; Manson, JoAnn E.; Tobias, Deirdre K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Branched-chain amino acids (BCAAs; isoleucine, leucine, and valine) correlate with insulin resistance and poor glucose control, which may in part explain associations between type 2 diabetes and cardiovascular disease. However, the relationships of BCAAs with other cardiometabolic pathways, including inflammation and dyslipidemia, are unclear. We hypothesized that plasma BCAAs would correlate with multiple pathways of cardiometabolic dysfunction. Methods: We conducted a cross-sectional analysis among 19 472 participants (mean age=54.9 years, SD=7.2 years) in the Women's Health Study without a history of type 2 diabetes, cardiovascular disease, or cancer. We quantified the concentrations of individual biomarkers of inflammation and lipids, across quartiles of BCAAs, adjusting for age, smoking, body mass index, physical activity, and other established cardiovascular disease risk factors at blood draw. Results: Women in the highest versus lowest quartiles of plasma BCAAs had higher inflammatory markers including high-sensitivity C-reactive protein (multivariable-adjusted means: 1.96 versus 1.43 mg/L), fibrinogen (367 versus 362 mg/dL), soluble intercellular cell adhesion molecule-1 (361 versus 353 ng/mL), and glycoprotein acetylation (407 versus 371 µmol/L; P trend=0.0002 for fibrinogen; P <0.0001 for others). Similarly for lipids, women with higher BCAAs had lower HDL-C (high-density lipoprotein cholesterol; 49.0 versus 55.0 mg/dL), and higher triglycerides (143 versus 114 mg/dL), LDL-C (low-density lipoprotein cholesterol; 133 versus 124 mg/dL), and lipoprotein insulin resistance score (52.6 versus 37.3; all: P <0.0001). Similar associations with these biomarkers were observed in isoleucine, leucine, and valine, respectively. Conclusions: Higher circulating BCAA concentrations are associated with adverse profiles of biomarkers of inflammation and dyslipidemia independent of established cardiovascular disease risk factors, and thus, may reflect poorer cardiometabolic health through multiple pathways. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00000479.